Strategy For Using Social Media As A Means Of Marketing Mist Of Rainbow Waterfall - Sahrullah, Ahmad; Sholehah, Mir’atus; Ar-Royyan Fahmiansyah, Muhammad Abyan; Bachrul Ulum, Muhammad; Hadiniyah, Nur; Dewi, Rosy Kusuma; Iksan, Sayid Zainul; Yusrianti, Yusrianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Lumajang Regency, East Java, has significant natural tourism potential, including Kabut Pelangi Waterfall in Sidomulyo Village. However, this destination is not yet widely known. This study aims to enhance the visibility of Kabut Pelangi Waterfall through social media platforms such as YouTube, Instagram, Facebook, and TikTok. Using descriptive and qualitative methods along with the Asset Based Community Development (ABCD) approach, data were collected through observations, interviews, and content analysis of social media. The research findings indicate that social media is effective in promoting this destination, as evidenced by positive responses and increased public interest. With the right marketing strategy, Kabut Pelangi Waterfall can attract more visitors, support the local economy, and serve as an example for the development of other tourist attractions in Lumajang.